EXPLORING THE DRIVERS FOR HOUSEHOLD COOKING ENERGY TRANSITION IN GOMBE METROPOLIS, NIGERIA - Ahmed, A.; Isma’il, M.; Mohammed, H.; Zubairu, S. M.; Salim, A. A.; Hassan, A. W.; Umar, J. H.; Ibrahim, N. M.; Balarabe, A.; Yusuf, S. S.; Umar, K. S. (FUDMA JOURNAL OF SCIENCES, 2023)
Transition to sustainable energy in the household sector is a one-way solution to significantly reducing the contending problem of forest exploitation on one hand and on the other hand an important effort to minimizing the challenging subject of climate change. This study aimed at exploring the drivers for household cooking energy transition in Gombe metropolis with a view to providing detailed information on the transition pathways in the area for policy implications. The study used quantitative research method with structured questionnaire as the instrument for data collection, while secondary data was obtained from the Gombe State Bureau of Statistics. For data collection, systematic sampling strategy was used to select sampling locations and the households to be administered the questionnaire. The quantitative data was analysed using descriptive statistics and multinomial logistic regression analysis. Result from descriptive analysis revealed that household size (69.5%), households’ level of income (65.5%) and public influence (65.5%) were the major factors influencing modern energy choice in the study area on one hand and on the hand environmental consequences (35.8%), health risks (34%) and seasonal changes (49.5%) has no significant influence on household modern energy choice for cooking. Multinomial logistic regression analysis showed the likelihood of respondent’s socio-demographics and modern energy adoption (p-value <0.05). The study recommends conducting public awareness campaigns on the benefits of modern energy services for cooking through media and public gatherings. It also suggests providing adequate access to affordable modern energy to encourage households to adopt and shift to modern energy consumption for cooking.